CREATIVE DESIGN METHODS FOR IOT DATA ETHICS IN HYBRID SPACES - Jacobs, Naomi Jane; Kwon, Nuri; Mullagh, Louise (AoIR Selected Papers of Internet Research, 2023)
This paper presents the use of creative methods including walking workshops, design fiction and policy prototyping to investigate questions of trust, security and ethics in public space Internet of Things (IoT) deployments. We describe how the walking workshops, or ’walkshops’, were developed to incorporate both real IoT deployments, and design fictions representing mundane speculations, in the context of a city in the North-West of England. The first event was held in the physical city, highlighting its hybrid nature as ubiquitous data collection becomes common. The event was also repeated in a digital hybrid space created for this purpose which replicated the features of the city walk virtually. These activities were used to engage with local council officers and cybersecurity experts, and supported the development of new local government policies for secure and ethical IoT deployment. The outcomes of this work include reflections on the use of these methods, the delivery of policy recommendations, and the development of an online tool to support organizations in consideration of IoT deployments. Potential users of this tool include public bodies evaluating whether or not deployments conform to policy, those undertaking the design or procurement process for a deployment, and any other organizations assessing ethical and security aspects of IoT. We reflect on how combining such creative methods with others such as speculative design allows us a deeper insight into questions of data ownership, ethical data practice and data governance.